Sistematic Literature Review: Etika Kepemimpinan pada Industri Penerbangan - Krisman, Muhammad Rafli; Rany Adiliawijaya Putriekapuja (Jurnal Bisnis dan Operasi Penerbangan, 2024)
This article investigates the crucial role of ethical leadership in the aviation industry, which operates in a complex and risky environment. It focuses on integrity, responsibility, and their impact on safety culture and organizational performance. The research employs the Systematic Literature Review (SLR) method to explore relevant literature. Findings indicate that leaders in the aviation industry must possess high administrative skills and strong moral integrity. Ethical leadership plays a vital role in ensuring operational safety and employee well-being. Research results suggest that leaders who practice ethical leadership tend to create safer and more productive work environments. The research methodology begins with formulating clear research questions regarding ethical leadership in the aviation industry. Literature search is conducted systematically using relevant academic databases and appropriate keywords to identify relevant studies. Selected articles are evaluated for methodological quality and relevance to the research topic. Information gathered from these articles is synthesized to present key findings and implications for leadership practices in the aviation industry. The article concludes that integrity, responsibility, and safety are key aspects of ethical leadership in the aviation industry. Leaders who practice ethics can positively influence safety culture and organizational performance. Therefore, it is crucial for leaders in the aviation industry to prioritize integrity and responsibility in their leadership practices to support sustainable progress in aviation business.